제주지역 젊은 성인의 배달음식 섭취실태와 식생활 및 비만과의 연관성 - 고민정(Minjung Ko); 하경호(Kyungho Ha) (Journal of nutrition and health, 2024)
Purpose: The use of food delivery services is increasing continuously in Korea, which may lead to nutritional problems and obesity. Despite this, the research on the association between delivered food consumption and obesity has been insufficient. This study examined the relationship between delivered food consumption and dietary behaviors and obesity among young adults in Jeju. Methods: An online survey was conducted from March 15 to April 5, 2023; 312 participants aged 19-39 years were included in the final analysis. The frequency, types, and time of delivered food consumption were measured using a questionnaire. The dietary behaviors included the following: eating out, breakfast consumption, recognition of nutrition labels, and eating salty foods, vegetables, and fruit. Obesity was defined using the body mass index based on self-reported body weight and height. Results: Approximately 59.3% of the participants ordered delivery foods more than one time/week. The frequency of delivered food consumption was higher in people who consumed breakfast < 5 times/week than those who consumed ≥ 5 times/week (p = 0.0088). People who usually eat salty foods tended to consume delivered food more frequently than those who did not (p = 0.0377). On the other hand, people who consumed fruits ≥ 1 time/day had a higher frequency of delivered food consumption than those who consumed fruits < 1 time/day (p = 0.0110). After adjusting for the confounding variables, the group who consumed delivered foods more than three times/week had an increased odds ratio (OR) of obesity compared to those who consumed less one time/week (OR, 2.38; 95% confidence intervals, 1.12-5.06). Conclusion: Young adults in Jeju who frequently consume delivered foods tended to have poor dietary habits including skipping breakfast and eating salty, and they had an increased odds of obesity. The overall dietary patterns can be improved by providing nutrition education and developing policies to promote or support healthy food choices when ordering delivered foods or eating out. 본 연구는 제주지역 20-30대 성인 312명의 배달음식 섭취 실태를 파악하고, 이에 따른 식생활 및 비만과의 연관성을 규명하고자 하였다. 조사참여자의 배달음식 섭취 빈도는 '주 1-2회(32.37%)'가 가장 높았으며, 다음으로 월 1-3회 (32.05%)', '주 3-4회 (20.51%)순으로 높았다. 아침식사 섭취빈도가 높을수록 배달음식 섭취 빈도가 낮게 나타났으며, 평소 짜게 먹을수록 배달음식 섭취 빈도가 높게 나타났다. 조사대상자의 비만 여부에 따른 배달음식 섭취빈도 분석 결과, 비만한 그룹에서 배달음식을 주 3회 이상 섭취하는 비율 (40.00%)이 비만하지 않은 그룹 (23.38%)에 비해 높았고, 배달음식을 주 1회 미만 섭취하는 비율은 비만하지 않은 그룹(45.02%)에서 비만한 그룹 (28.00%)에 비해 높았다. 배달음식 섭취빈도와 비만과의 연관성을 알아보기 위해 다중 로지스틱 회귀분석을 실시한 결과 배달음식을 주 1회 미만 섭취하는 경우에 비해 주 3회 이상 섭취할 경우 비만의 교차비가 2.4배 더 유의하게 높았다. 이상과 같은 결과를 토대로 할 때 제주지역 젊은 성인에서 배달음식을 자주 섭취할수록 아침결식, 평소 짜게 먹는 등 식생활이 바람직하지 않았고, 비만의 위험이 높았다. 본 연구의 결과는 배달음식 소비자 측면에서 건강한 음식 선택 및 섭취를 위한 영양지식 증가의 필요성을 시사한다. 배달시장 측면에서는 배달음식의 종류가 다양화됨에 따라 건강식에 대한 수요가 높아지고 있으므로 건강 고려사항에 대한 옵션 강화가 요구되며, 배달음식 영양표시를 위한 정부 및 지자체의 지원이 필요할 것으로 사료된다.